Adv Alegbra HW Solutions 112 - 112(vi If f(x is a...

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 112 (vi) If f (x ) is a polynomial over a ﬁeld K whose factorization into a constant and monic irreducible polynomials in K [x ] is f (x ) = e e ap11 · · · pnn , and if all the coefﬁcients of f (x ) and of the polynoe e mials pi (x ) lie in some subﬁeld k ⊆ K , then f (x ) = ap11 · · · pnn is also the factorization of f (x ) in k [x ] as a product of a constant and monic irreducible polynomials. Solution. True. f f e e 3.83 In k [x ], where k is a ﬁeld, let g = p11 · · · pmm and h = p1 1 · · · pmm , where the pi ’s are distinct monic irreducibles and ei , f i ≥ 0 for all i . Prove that g | h if and only if ei ≤ f i for all i . Solution. The proof for polynomials is essentially the same as for integers. 3.84 (i) If f (x ) ∈ R [x ], show that f (x ) has no repeated roots in C if and only if ( f , f ) = 1. Solution. By part (ii), f (x ) has no repeated roots in C [x ] if and only if ( f , f ) = 1 in C [x ]. By Corollary 3.75, one can check this criterion by computing this gcd in R [x ]. (ii) Prove that if p (x ) ∈ Q [x ] is an irreducible polynomial, then p (x ) has no repeated roots. n n Solution. If p (x ) = i =0 ai x i , then p (x ) = i =1 iai x i −1 . It follows that deg( p ) = n − 1, and so p is not the zero polynomial. Since p(x ) is irreducible, the gcd ( p , p ) = 1, and so part (ii) applies to show that p (x ) has no repeated roots. Note that this argument may fail if Q is replaced by F p , where p is prime. 3.85 Let ζ = e2π i / n . (i) Prove that x n − 1 = (x − 1)(x − ζ )(x − ζ 2 ) · · · (x − ζ n −1 ) and, if n is odd, that x n + 1 = (x + 1)(x + ζ )(x + ζ 2 ) · · · (x + ζ n −1 ). Solution. The n numbers 1, ζ, ζ 2 , . . . , ζ n −1 are all distinct. But they are all roots of x n − 1, and so Theorem 3.50 gives the ﬁrst equation: x n − 1 = (x − 1)(x − ζ )(x − ζ 2 ) · · · (x − ζ n −1 ). If n is odd, then replace x by −x to get (−x )n − 1 = (−x − 1)(−x − ζ )(−x − ζ 2 ) · · · (−x − ζ n −1 ) = (−1)n (x + 1)(x + ζ )(x + ζ 2 ) · · · (x + ζ n −1 ). ...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online